Humanization of Arabic Islamic Architecture - Abdullah Saadoon Salman Almaamouri (Iraqi Journal of Architecture and Planning, 2018)
Architecture is the content of human events, it is the most important products through history with all its structure of the formal elements, relations between them and the regulations governing the organization of space and movement patterns and formations that form the lives of their inhabitants to achieve the highest performance of the material without displacing the local building techniques and modern engineering into account the rules and the investment component of the site in order to find the structure of architectural humanism the surrounding elements of the natural environment to achieve the requirements basic, so the architecture is the spatial - temporal extension to accommodate the integrated human concept and has an amount of the relative stability of its components being subject to the values, conventions and beliefs.The environment of contemporary architecture Suffered from a clear separation between human values system and product architecture, the research's aim, which is :" study the requirements of the basic need which is supposed to be available in the to access the humanization architecture inspired by the Arab-Islamic architectural heritage, to achieve the integrated architectural environment and maintain an identity and privacy", Accordingly, the research's problem was reflected in : "The environment of contemporary architecture losses the humanity, identity and their inability to achieve integration between the product architecture and the requirements of the need" . So the research shed light on the basic requirements and privacy associated with the humanize the architectural product which is clearly reflected in the characteristics of the Arab-Islamic architecture,the way to the final conclusions and recommendations .